Coexistence of anti‐MDA5 and anti‐PL‐7 in a patient with dermatomyositis: A case report. Issue 1 (23rd January 2023) - Fu, Hongyan; Sun, Shaofeng; Zhang, Hong; Chi, Shuhong; Ma, Weirong; Yang, Guilan; Chen, Juan
Abstract: Coexisting anti‐MDA5 and anti‐PL‐7 antibodies are extremely rare. Anti‐MDA5 is associated with rapidly progressive interstitial lung disease (RP‐ILD), while anti‐PL‐7 is often associated with chronic or subacute ILD and better outcomes than RP‐ILD. We report a 41‐year‐old woman diagnosed with dermatomyositis (DM)‐associated ILD positive for anti‐MDA5 and anti‐PL‐7. Abstract : The coexistence of anti‐MDA5 and anti‐PL‐7 antibodies is extremely rare. We report a 41‐year‐old woman with coexisting anti‐MDA5 and anti‐PL‐7 and the patient had an effective response to treatment.